High resolution pull-in inclinometer - Alves, F. S. (2013)
A MEMS high-resolution inclinometer is presented in this paper. Unlike traditional approaches, a transduction mechanism based on the measurement of pull-in voltages is used for the realization of the sensor. The advantage is on-device capability for auto-calibration and thermal compensation, and more relaxed specifications for the capacitive readout electronics. In addition, dedicated MEMS microstructures with extra proof-mass are proposed and tested for high-resolution applications. The microstructures have differential actuation electrodes (with a common electrode) resulting in two pull-in voltages that change differentially with applied acceleration. The device shows a sensitivity of 300 mV/º with a non-linearity below 0.5%FS (Full Scale of ±10º). The measured noise level of 3mV sets the system resolution at 0.01º, above the theoretical resolution limit of 0.001º (due to the actuation voltage resolution of 300μV).